Veterans' Urgent Care Use and Subsequent Utilization in the Community - Farai M. Kuwonza; Sivagaminathan Palani; Kristina Smith; Steven D. Pizer (Health Services Research, 2026)
ABSTRACT Objective To evaluate the impact of Veterans' urgent care use in non‐Veterans Health Administration (VHA) clinics on their later use of specialty and emergency care. Study Setting and Design A retrospective cohort study analyzing urgent care, specialty care, and emergency department (ED) visits using VHA administrative and claims data. Veterans' first urgent care visit was the index visit, and subsequent utilization was tracked for up to 1 year. We used an instrumental variable (IV) approach to estimate the effect of non‐VHA urgent care visits on the proportion of subsequent visits in non‐VHA clinics. Data Sources and Analytic Sample We used VHA administrative and community care claims data (2021–2022) obtained from the Corporate Data Warehouse. Our sample comprised VHA enrollees with at least one urgent care visit at a VHA or non‐VHA urgent care clinic in 2021. Principal Findings Of the 111,898 Veterans in the sample, 90,651 (81%) had their urgent care visit in the VHA, while 21,247 (19%) visited a non‐VHA clinic. IV models showed that Veterans using non‐VHA urgent care had 40 percentage points higher proportions of non‐VHA specialty care within 30 days compared to those using VHA (95% CI: 37, 43). Effects stabilized at 28 percentage points within 365 days post urgent care visit (95% CI: 26, 30). In contrast, the effect of community urgent care on subsequent ED use outside the VHA system after 30 days of urgent care use was negligible and statistically insignificant. Conclusions Veterans' use of non‐VHA urgent care can lead to increased subsequent use of non‐VHA specialty care but has no effect on non‐VHA emergency care utilization within 60 to 365 days after urgent care visit. While expanded community care improves access in the short run, it also introduces care coordination challenges throughout an episode of care that may negatively affect health outcomes.